Bell's palsy in a child with acute viral hepatitis C infection - Neha Thakur; Narendra Rai (Wolters Kluwer Medknow Publications, 2021)
Background: Bell's palsy is the most common form of facial paralysis in children. Etiology of facial paralysis can be both congenital and acquired. Acquired facial paralysis in most cases is due to viral infections. Hepatitis C infection leading to Bell's palsy is an unusual complication which has not been reported until now. Clinical Description and Management: A 4 month's old male child was admitted with fever, vomiting, refusal to feed, and icterus. His investigations revealed anemia with neutrophilic leukocytosis and deranged liver function tests. Hepatitis C antibody test was reactive. On 5th day of admission, right-sided Bell's palsy was noticed. There were no other signs of neurological deficit. Parental testing revealed hepatitis C antibodies in mother. The child was managed conservatively. He responded to treatment and symptoms subsided within 1 week of its onset. Conclusion: This case report highlights an unusual complication of hepatitis C infection in children. Prognosis in this case was good as the child recovered spontaneously.